The reduced folate carrier (SLC19A1) c.80G>A polymorphism is associated with red cell folate concentrations among women. - SCOTT, JOHN MARTIN (Wiley-Blackwell, 2009)
Low folate status may be a consequence of suboptimal intake, transport or cellular utilization of folate and, together with elevated homocysteine, is a recognized risk factor or marker for several human pathologies. As folate transport across cell membranes is mediated in part by the reduced folate carrier (RFC1), variants within SLC19A1, the gene that encodes RFC1, may influence disease risk via an effect on folate and/or homocysteine levels. The present study was undertaken to assess the association between the SLC19A1 c.80G>A polymorphism and folate/homocysteine concentrations in healthy young adults from Northern Ireland. The SLC19A1 c.80G>A polymorphism was not strongly associated with either serum folate or homocysteine concentrations in either men or women. However, in women, but not in men, this polymorphism explained 5% of the variation in red blood cell (RBC) folate levels (P= 0.02). Relative to women with the SLC19A1 c.80GG genotype, women with the GA and AA genotypes had higher RBC folate concentrations. Consequently, compared to women with the SLC19A1 c.80GA and AA genotypes, women who are homozygous for the 80G allele may be at increased risk of having a child affected with a neural tube defect and of developing pathologies that have been associated with folate insufficiency, such as cardiovascular disease.
PUBLISHED
Keywords: Reduced folate carrier; Folate; Homocysteine